The Comparison of Dynamic Relationship between Sharia Stock Index and Composite Index with Macroeconomic Variables: A Case Study of Indonesia - Agus Herta Sumarto (Universitas Mercu Buana, 2021)
This research analyses the dynamic relationship between sharia stock exchange (ISSI) and macroeconomics condition then it would be compared to the relationship of the composite stock exchange (IDX Composite Stock). The method used in this study is Dynamic Conditional Correlation (DCC) analysis. Based on DCC method, it seems that macroeconomic variable have changing pattern of correlation relationship. This changeable pattern is not only on value scale but until its number sign. It indicated that macroeconomic variable has not any significant impact on sharia stock index (ISSI) and IDX composite index and vice versa.